Preferensi Masyarakat tentang Lingkungan Perumahan yang Ingin Ditinggali - Syafrina, Andina; Tampubolon, Angela Christysonia; Suhendri, Suhendri; Hasriyanti, Nunik; Kusuma, Hanson Endra (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2018)
Housing development needs to be supported by particular guidelines issued by authorized institute for the achievement of development feasibility. Community participation as the main actors and users also took an important part for housing development to fit the target. Community disappointment is often caused by results that do not match the desires or not according to standards. The aim of this study was to find the preferences of the community related to the housing environment to be occupied, so it can open the new possibility in planning and designing the housing environment. This research uses exploratory qualitative and grounded theory method. Data collection is done through an open-ended online questionnaire and shared freely (non-random sampling). The collected data was analyzed qualitatively using the content analysis methods. The result showed that the five aspects that become the preference of residential environment (5 PRE) namely: environmental comfort, environmental facilities, environmental infrastructure, location and accessibility, building and residential environment design.